2018
DOI: 10.3389/fonc.2018.00114
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Therapeutic Efficacy of Cancer Treatment With Cannabinoids

Abstract: Over the years, many in vitro and in vivo studies have shown the antineoplastic effects of cannabinoids (CBDs), with reports advocating for investigations of combination therapy approaches that could better leverage these effects in clinical translation. This study explores the potential of combination approaches employing CBDs with radiotherapy (RT) or smart biomaterials toward enhancing therapeutic efficacy during treatment of pancreatic and lung cancers. In in vitro studies, clonogenic assay results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 30 publications
(40 reference statements)
3
45
0
Order By: Relevance
“…A study by Yasmin-Karim et al revealed that a superior pancreatic cancer treatment outcome could be achieved using the combination of cannabinoids and radiotherapy. 7 Similar findings have been demonstrated in a brain glioma cancer model. 67 Improved survival was also demonstrated with IT administration of cannabinoids into subcutaneously implanted murine PANC-02 pancreatic cancers measuring 6 mm in maximum dimension.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…A study by Yasmin-Karim et al revealed that a superior pancreatic cancer treatment outcome could be achieved using the combination of cannabinoids and radiotherapy. 7 Similar findings have been demonstrated in a brain glioma cancer model. 67 Improved survival was also demonstrated with IT administration of cannabinoids into subcutaneously implanted murine PANC-02 pancreatic cancers measuring 6 mm in maximum dimension.…”
Section: Resultssupporting
confidence: 76%
“…67 Improved survival was also demonstrated with IT administration of cannabinoids into subcutaneously implanted murine PANC-02 pancreatic cancers measuring 6 mm in maximum dimension. 7 Furthermore, treating Kras, P53, and Cre mice with a combination of CBD (100 mg/kg) by daily intraperitoneal (IP) administration and gemcitabine (100 mg/kg) by IP administration every 3 days, IP after 80 days of age prolonged the animal survival three times more than vehicle or gemcitabine treatment alone. 61…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AEA inhibits the proliferation of breast cancer cells through nerve growth factor (NGF) and prolactin, by downregulating the NGF receptor and prolactin receptor, respectively [69]. The inhibitory effect of AEA on prolactin receptors may regulate the cancer-directed immune system, as prolactin is a potent endogenous proliferative agent of B and T cells [70]. Furthermore, AEA inhibits cell cycle progression by preventing G1/S transition, as demonstrated in the human prolactin sensitive breast epithelioid EFM-19 cell line [70].…”
Section: Cannabinoids In Breast Cancermentioning
confidence: 99%
“…The inhibitory effect of AEA on prolactin receptors may regulate the cancer-directed immune system, as prolactin is a potent endogenous proliferative agent of B and T cells [70]. Furthermore, AEA inhibits cell cycle progression by preventing G1/S transition, as demonstrated in the human prolactin sensitive breast epithelioid EFM-19 cell line [70]. Similar to AEA, the endocannabinoid 2-AG also exerts antiproliferative activity in MCF-7 and T-47D cells [69], as well as in EMG-19 breast cancer cells [70].…”
Section: Cannabinoids In Breast Cancermentioning
confidence: 99%